DESAFIOS PARA A IMPLANTAÇÃO DE UM PLANO DE COMUNICAÇÃO INTERNA EM UM ÓRGÃO PÚBLICO FEDERAL - Reinaldo, Priscila (2009)
The proposal of this study is to analyze the implementation of an internal communication plan designed for a Brazilian federal institution. It is a case study that seeks to identify the initial difficulties related to the introduction of a system of internal communication in a public institution that holds a history of extensive changes and an organizational culture in process of change. The research universe was the Gerência Regional of the Instituto Nacional do Seguro Social (INSS) in São Paulo and its employees, including those who were already working in the areas of social communication. As a result of the study, was presented an analysis of the situation, with details of the internal communication plan developed and observations on the difficulties found during the implementation of this plan, which aimed to optimize the key processes and flows of communication within the organization studied.